Long-term durability assessment of PVC-P waterproofing geomembranes through laboratory tests. (September 2020) - Luciani, Andrea; Todaro, Carmine; Martinelli, Daniele; Peila, Daniele
Highlights: Plasticizer loss is the main phenomenon affecting the durability of PVC membranes. A device for accelerated ageing tests on PVC membranes has been developed. Mechanical tests are performed to study the time-dependent properties of membranes. Plasticizer loss with time has been modelled from plasticizer absorption tests data. The end-of-life time of the two commercial PVC membranes is evaluated. Abstract: Waterproofing heavily influences the operation and maintenance costs of underground structures. Currently, the most commonly used technology for tunnel waterproofing is plasticized polyvinyl chloride (PVC-P) geomembranes. However, not much is known about the long-term durability of these geomembranes, especially in relation to the long expected lifespan of new tunnels (i.e. 100–150 years). Therefore, in this paper, the durability of two commercially available PVC-P geomembranes is studied with the help of a specifically designed accelerated ageing device in addition to mechanical and absorption tests. The degradation resulting from plasticizer loss is extrapolated to the long term, and a threshold value for the end-of-life of the PVC-P geomembrane is estimated from the mechanical tests.